2012
DOI: 10.1080/15487733.2012.11908098
|View full text |Cite
|
Sign up to set email alerts
|

Creating the future we want

Abstract: Although the world faces serious environmental, economic, and social challenges, we believe that a combination of science and innovation, effective governance, and public-private collaboration can help to overcome many of them and achieve sustainable development. Numerous government policies are now promoting sustainable management practices, while many people in the business and financial communities view sustainability as a means to reduce long-term risk, enhance competitiveness, and promote social well-bein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 8 publications
0
13
0
Order By: Relevance
“…For cadastral mapping, numerous studies have demonstrated the potential of UAVs especially in terms of fast data capturing and high accuracy [40]. UAV-based cadastral mapping could contribute to contemporary initiatives such as the United Nations' sustainable development goals, as it allows a new economic, environmental and social approach to cadastral mapping [228]. With UAVs being able to rapidly map small areas, the cadastral map could be kept up-to-date at low-cost in a sustainable way.…”
Section: Discussionmentioning
confidence: 99%
“…For cadastral mapping, numerous studies have demonstrated the potential of UAVs especially in terms of fast data capturing and high accuracy [40]. UAV-based cadastral mapping could contribute to contemporary initiatives such as the United Nations' sustainable development goals, as it allows a new economic, environmental and social approach to cadastral mapping [228]. With UAVs being able to rapidly map small areas, the cadastral map could be kept up-to-date at low-cost in a sustainable way.…”
Section: Discussionmentioning
confidence: 99%
“…Businesses and industries are generally seen as the driving force of green economy transitions, while the role of governments is to guide these with effective policies and regulations, including support to innovation (Hecht et al 2012). It has been further noted that governments should systematically encourage and create sustainable industries covering all types of services and technologies, and promote sustainable consumption and production overall.…”
Section: Role Of the State And Its International Relationsmentioning
confidence: 99%
“…The conclave resulted in governments and businesses making over 700 pledges to action, amounting to approximately $500 billion. The outcome of this meeting clearly demonstrated the global business commitment to achieving sustainable practices, as well as the importance of business-government collaboration (Hecht et al 2012).…”
mentioning
confidence: 92%